If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 14 + -3y = -7 Solving 14 + -3y = -7 Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '-14' to each side of the equation. 14 + -14 + -3y = -7 + -14 Combine like terms: 14 + -14 = 0 0 + -3y = -7 + -14 -3y = -7 + -14 Combine like terms: -7 + -14 = -21 -3y = -21 Divide each side by '-3'. y = 7 Simplifying y = 7
| -3k-39=-5(8k-7) | | -6(1+7a)=27 | | 4t(5t-4t)=0 | | 5/2x=0 | | 65ab^3-45a^2b^2=0 | | 16=9x+2-2x | | 5.4x=7.02 | | 5n^2-16n=-3 | | 7x-8=x+7 | | 0.15(x+10)=8x+20 | | 5-2a=5a-2 | | -1(3x+4)-4r=-2(4r-3)+2 | | 2x+5=6x-9 | | x+-2x+4=3 | | 16+5a=56 | | x^2+4x+4y^2=0 | | 6x+14=5x+12 | | 3(m^2+10m+23)=0 | | r^2+3r=10 | | 7a-7+6a=10-4a | | 3x^2+11x-1-x^3=0 | | y=-2(x+3)2+2 | | x/2=20/10 | | 10t+3(1-4t)= | | x-59=-24 | | A=3.14r*2(5) | | 8m=-14-30 | | x^(2/3)e^x | | 6.5x=7.8 | | 16-4=3x+8-6 | | 4x+4+2x+1= | | .2x+104.8=102 |